2016
DOI: 10.1590/1414-431x20165542
|View full text |Cite
|
Sign up to set email alerts
|

ADME studies and preliminary safety pharmacology of LDT5, a lead compound for the treatment of benign prostatic hyperplasia

Abstract: This study aimed to estimate the absorption, distribution, metabolism and excretion (ADME) properties and safety of LDT5, a lead compound for oral treatment of benign prostatic hyperplasia that has previously been characterized as a multi-target antagonist of α1A-, α1D-adrenoceptors and 5-HT1A receptors. The preclinical characterization of this compound comprised the evaluation of its in vitro properties, including plasma, microsomal and hepatocytes stability, cytochrome P450 metabolism and inhibition, plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This concern is also strengthened by the relatively high affinity we reported here for LDT5 binding to the D 3 receptor. Considering these data, LDT5 is no more considered as the ideal lead compound since the permeability assay with MDCK-MDR1 showed that it is not a substrate of P-glycoprotein (Noël et al, 2016). However, we suggest that the rationale of such a multitarget drug for BPH treatment is maintained mainly based on our previous data with cells from BPH patients, since LDT5…”
Section: Discussionmentioning
confidence: 98%
“…This concern is also strengthened by the relatively high affinity we reported here for LDT5 binding to the D 3 receptor. Considering these data, LDT5 is no more considered as the ideal lead compound since the permeability assay with MDCK-MDR1 showed that it is not a substrate of P-glycoprotein (Noël et al, 2016). However, we suggest that the rationale of such a multitarget drug for BPH treatment is maintained mainly based on our previous data with cells from BPH patients, since LDT5…”
Section: Discussionmentioning
confidence: 98%
“…SCREENER has been conceived as a collaborative project between people with experience on the theoretical aspects of the theme ( 8 - 10 ), experts in ludology with prior experience in game designing and production ( 13 ), and people from the artistic design field. The idea matured after five years of using a board game in a discipline of the Postgraduate Program in Pharmacology and Medicinal Chemistry (PPGFQM) at the Federal University of Rio de Janeiro, Brazil.…”
Section: Methodsmentioning
confidence: 99%